Primary Repair of Posteriorly Located Anterior Skull Base Dural Defects Using Nonpenetrating Titanium Clips in Cranial Trauma - Milton, Camille K.; Andrews, Bethany J.; Baker, Cordell M.; O'Connor, Kyle P.; Conner, Andrew K.; Sughrue, Michael E.; McKinney, Kibwei A.; El Rassi, Edward T.; Sanclement, Jose A.; Glenn, Chad A. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Primary repair of posteriorly located anterior skull base (ASB) dural defects following cranial trauma is made difficult by narrow operative corridors and adherent dura mater. Inadequate closure may result in continued cerebrospinal fluid (CSF) leak and infectious sequelae. Here, we report surgical outcomes following the use of nonpenetrating titanium microclips as an adjunctive repair technique in traumatic anterior skull base dural defects extending from the olfactory groove to the tuberculum sellae.Methods All trauma patients who underwent a bifrontal craniotomy from January 2013 to October 2019 were retrospectively reviewed. Patients with ASB defects located at posterior to the olfactory groove were analyzed. Patients with isolated frontal sinus fractures were excluded. All patients presented with CSF leak or radiographic signs of dural compromise. Patients were divided according to posterior extent of injury. Patient characteristics, imaging, surgical technique, and outcomes are reported.Results A total of 19 patients who underwent a bifrontal craniotomy for repair of posteriorly located ASB dural defects using nonpenetrating titanium microclips were included. Defects were divided by location: olfactory groove (10/19), planum sphenoidale (6/19), and tuberculum sellae (3/19). No patients demonstrated a postoperative CSF leak. No complications related to the microclip technique was observed. Clip artifact did not compromise postoperative imaging interpretation.Conclusion Primary repair of posteriorly located ASB dural defects is challenging due to narrow working angles and thin dura mater. Use of nonpenetrating titanium microclips for primary repair of posteriorly located dural defects is a reasonable adjunctive repair technique and was associated with no postoperative CSF leaks in this cohort.
Keywords: trauma; dural closure; durotomy; nonpenetrating titanium clips; skull base